"We Are Dying!" On Death Signals of Software Ecosystems - Soupinski, Felipe; Arantes, Pedro; Steinmacher, Igor; Wiese, Igor; Borges, Hudson; Cafeo, Bruno; Fontão, Awdren (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Software Ecosystems (SECO) depend on platforms that serve as environments for developers interaction. When the organization that owns the platform does not support the synergy between organizational goals and developers’ expectations, the SECO may die. The death results in the definitive suspension of vital activities, directly impacting developers, who lose part of the learning and experience gained. Projects that depend on the SECO platform may be discontinued. Ultimately, the responsible corporation loses the resources invested in the development and maintenance of the software and communities. Thus, understanding the signs that may indicate a SECO death is important. In this paper, we report a study conducted on StackOverflow (SO) and GitHub (GH) focusing on Web SECOs: AngularJS, PhantomJS, and Moment.JS. We analyzed metrics based on answer rates, closed issues, and modified files to understand what happens in these SECOs before, during, and after the platform’s death. We identified that an SO answer rate below 0.8 is a sign of risk. In GH, the files that involve source code and text are the ones that concentrate on the activities before and during death.